2016
DOI: 10.1017/s1365100515000796
|View full text |Cite
|
Sign up to set email alerts
|

On the Interaction Between Economic Growth and Business Cycles

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 96 publications
(166 reference statements)
0
2
0
Order By: Relevance
“…Other studies (IMF , 2010;Klump et al , 2008;León-Ledesma and Thirlwall , 2002;Mendieta-Muñoz , 2017;Schnabel , 2002;Thirlwall , 1969) have also identified the rate of growth consistent with a constant unemployment rate derived from the first difference version of Okun's law as a measure of a "potential" or "natural" output growth rate, without focusing on the evolution of the latter over time. The term "natural" stems from Roy Harrod's theoretical studies on the business cycle, who defined the natural rate of growth as the "the maximum rate of growth allowed by the increase of population, accumulation of capital, technological improvement and the work leisure preference schedule, supposing that there is always full employment in some sense" (Harrod , 1939: 30).…”
Section: Okun's Law and Long-run Output Growth Ratesmentioning
confidence: 99%
“…Other studies (IMF , 2010;Klump et al , 2008;León-Ledesma and Thirlwall , 2002;Mendieta-Muñoz , 2017;Schnabel , 2002;Thirlwall , 1969) have also identified the rate of growth consistent with a constant unemployment rate derived from the first difference version of Okun's law as a measure of a "potential" or "natural" output growth rate, without focusing on the evolution of the latter over time. The term "natural" stems from Roy Harrod's theoretical studies on the business cycle, who defined the natural rate of growth as the "the maximum rate of growth allowed by the increase of population, accumulation of capital, technological improvement and the work leisure preference schedule, supposing that there is always full employment in some sense" (Harrod , 1939: 30).…”
Section: Okun's Law and Long-run Output Growth Ratesmentioning
confidence: 99%
“…In other words, if country authorities focus on the short-term behavior of the debt ratio, they may engage in repeated rounds of tightening in an effort to make the debt ratio converge with the official target, thereby undermining confidence and setting off a vicious circle of slow growth, deflation, and further tightening. Finally Mendieta-Muñoz (2014) showed that short-run fluctuations may affect the rate of growth. He studied 13 Latin American and 18 OECD economies during the period 1981-2011 and found evidence that business cycle fluctuations have significant impact on the rate of growth for the majority of studied economies.…”
Section: Introductionmentioning
confidence: 99%